Effects of in situ shading on the photophysiology of Zostera marina and Cymodocea nodosa - Silva, João (2010)
The effects of light reduction were investigated in natural stands of the seagrasses Zostera marina and Cymodocea nodosa in Ria Formosa coastal lagoon, southern Portugal. Four shading plots and a control were set in each of two neighbouring meadows (2-3 m depth), each dominated by one species. The experiment lasted for 3 weeks, at the end of which the response of plant photosynthesis to light was determined via oxygen electrode measurements. Tissue samples were also analysed for photosynthetic pigment, soluble protein, soluble sugar and malondialdehyde contents. All plants presented a shade-adapted profile, mostly revealed by their biochemical composition. In both species the chlorophyll a/chlorophyll b ratio decreased sharply whereas the total chlorophyll/total carotenoids and the total chlorophyll/soluble protein ratios increased. Soluble protein content was reduced more noticeably in Z. marina. Soluble sugars dropped almost 40% in Z. marina leaves and roots, a more pronounced effect than the one observed in C. nodosa. Overall, Z. marina revealed to be more sensitive than C. nodosa to reductions in incident irradiance, suggesting that it will be more sensitive to human-induced disturbances that result in an increase of water turbidity.